Digital Marketing, Brand Image, and Tourist Engagement as Determinants of Tourists’ Visit Intention: An Empirical Study of Cirebon Batik Cultural Tourism - Etty Zuliawati Zed; Sesri Sellina; Febri Sari Siahaan; Suherdi Maulana (Majapahit Journal of Islamic Finance and Management, 2026)
The rapid growth of digital technology has transformed the tourism industry by changing how tourists search for information and make travel decisions. In cultural tourism destinations, digital marketing, brand image, and tourist engagement are considered important factors influencing tourists’ behavioral intentions. This study aims to examine the effects of Digital Marketing, Brand Image, and Tourist Engagement on tourists’ visit intention toward Cirebon Batik Cultural Tourism, particularly in the Trusmi Batik Area and Kampung Batik Ciwaringin. A quantitative approach with an explanatory research design was employed. Data were collected from 220 respondents using a structured questionnaire distributed through Google Forms. The study utilized purposive sampling and analyzed the data using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The measurement model was evaluated through tests of validity and reliability, while the structural model was assessed using bootstrapping procedures. This research contributes to the tourism and marketing literature by extending the application of the Theory of Planned Behavior in cultural tourism contexts and providing insights for destination managers in developing effective strategies to enhance tourists’ intention to visit cultural heritage destinations.